Effects of Simulated Video Consultation Training on Nursing Students' Clinical Decision Making, Self-Confidence, and Anxiety: A Quasi-Experimental Study. - Tort-Nasarre, Glòria; Baltasar-Bagué, Alícia; Malagón-Aguilera, Maria del Carmen; Vilar-Pont, Mariona; Camí, Carla; Reig-Garcia, Glòria (Nursing Reports, 2026)
Background: The expansion of telenursing in primary care requires undergraduate nursing programmes to prepare students for clinical decision making in virtual care. However, evidence on educational interventions integrating clinical reasoning with managing uncertainty, anxiety, and self-confidence in telenursing remains limited. Objective: This study aims to assess changes in nursing students' self-confidence and anxiety related to clinical decision making following a simulation-based video consultation intervention, and to explore their satisfaction and perceived learning regarding this educational experience. Methods: A quasi-experimental pretest–post-test study with a comparison group was conducted at two public universities during the 2024–2025 academic year. Undergraduate nursing students (N = 115) were included. The intervention consisted of theoretical training on video consultations, complemented by structured simulated consultations based on primary care scenarios. The control group received no intervention. Outcomes were assessed before and after, with self-confidence and anxiety measured using the Nursing Anxiety and Self-Confidence with Clinical Decision Making (NASC-CDM©) scale. Satisfaction and perceived learning were evaluated in the intervention group using the Student Satisfaction and Self-Confidence in Learning Scale. Results: At baseline, students had high digital competence but limited preparedness for telenursing, with heterogeneous self-confidence and moderate anxiety in virtual decision making. After the intervention, the intervention group showed significant increases in self-confidence and reductions in anxiety, particularly in global clinical judgement and autonomous decision making. Students reported high satisfaction and perceived learning. Conclusions: Simulation-based video consultations may improve nursing students' self-confidence and reduce anxiety in virtual care decision making, suggesting a potentially valuable strategy for integrating psychoeducational dimensions into nursing curricula on digital health.